Anti-inflammatory and hepatoprotective activities of ethanolic extract of Euphorbia thymifolia linn - Singh S.K.; Prabha T.; Kavitha B.; Chouhan H.S.; Bharti S.K. (My University, 2025)
Euphorbia thymifolia Linn. (Euphorbiaceae) is a small prostate, hispidly pubescent, annual weed, which is commonly found in India and tropical countries. The plant is reported to be used in traditional medicine for the treatment of diarrhea, jaundice, pain etc. The aim of the present study was to evaluate the anti-inflammatory and hepatoprotective activities of ethanolic extract of whole plant. The anti-inflammatory effect was evaluated b carrageenan and cotton pellet induced rat models and hepatoprotective activity was accessed on CCl4-induced liver damage in rats. A dose dependent anti-edematogenic activity of ethanolic extract of E. thymifolia (dose of 200 mg/kg, p.o.) was observed and was comparable to Ibuprofen (dose of 50 mg/kg p.o.; p < 0.01) used as standard. The extract of the plant, screened for its hepatoprotective activity in CCl4 (0.5 ml/kg p.o.) induced liver damage in rats at a dose of 100 mg/kg p.o. The extract significantly (P < 0.01) normalized the serum enzymes alanine amino transferase (ALT) asparate amino transferase (AST) and lipid peroxidation (LPO) elevated b CCl4-toxicity, which was also supported by the histological examination of liver tissues. The hepatoprotective effect of the extract was comparable to that of silymarin (50 mg/kg p.o.) used as reference standard. The preliminar phytochemical screening of the ethanolic extract showed the presence of phenolics terpenes and flavonoids. Thus, the results validate the use of E.thymifolia in traditional medicines for the treatment of jaundice and inflammation related disorders.